2020
DOI: 10.1111/iej.13259
|View full text |Cite
|
Sign up to set email alerts
|

Palatogingival groove and root canal instrumentation

Abstract: Pinheiro TN, Cintra LTA, Azuma MM, Benetti F, Silva CC, Consolaro A. Palatogingival groove and root canal instrumentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
7
1
1
Order By: Relevance
“…[ 11 ] In a study by Pinheiro et al ., 70% of PGs were positioned along the distal root surface of the palatal side, followed by 20% in the central, and 10% in the mesial sides. [ 16 ] However, in the present study, 50% of the grooves were present in the mid-palatal surface of the teeth, 33% on distal aspect and 17% on the mesial aspect. Similar findings were reported by Hou and Tsai where 42.5% of PGs were positioned in the midpalatal surface, 30.1% on the distal aspect and 27.4% on the mesial aspect.…”
Section: Discussioncontrasting
confidence: 66%
“…[ 11 ] In a study by Pinheiro et al ., 70% of PGs were positioned along the distal root surface of the palatal side, followed by 20% in the central, and 10% in the mesial sides. [ 16 ] However, in the present study, 50% of the grooves were present in the mid-palatal surface of the teeth, 33% on distal aspect and 17% on the mesial aspect. Similar findings were reported by Hou and Tsai where 42.5% of PGs were positioned in the midpalatal surface, 30.1% on the distal aspect and 27.4% on the mesial aspect.…”
Section: Discussioncontrasting
confidence: 66%
“…Previous research has documented MLIs with RG, noting features such as prominent tubercles, exaggerated cingulums, and pronounced marginal ridges [1,10,15,24,25,29]. However, evaluating these characteristics with consistency posed challenges in our study.…”
Section: Discussionmentioning
confidence: 90%
“…PGG might be either unilateral or bilateral ( Everett and Kramer, 1972 , Jeng et al, 1992 , Peikoff et al, 1985 , Peikoff and Trott, 1977 ). Though the exact etiology of this anomaly is unclear, it has been suggested that it could be alterations during tooth development and growth, a mild form of dens invaginatus, or tooth attempts to form another root ( Gu, 2011 , Kim et al, 2017 , Peikoff et al, 1985 , Pinheiro et al, 2020 ). The clinical presentation of the defect is often on the palatal root surface, but, on some occasions, the involvement of the facial aspect has been reported ( Brin and Ben-Bassat, 1989 , Goon et al, 1991 , Kerezoudis et al, 2003 , Kozlovsky et al, 1988 ).…”
Section: Introductionmentioning
confidence: 99%
“…Smith & Carroll presented a case of maxillary lateral incisor with labial and palatal developmental grooves ( Smith and Carroll, 1990 ). Some studies indicated a tendency for proximal localization of PGG ( Albaricci et al, 2008 , Gu, 2011 , Pinheiro et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%